PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BAHASA INDONESIA KELAS VII DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH - Sri Rahayu (EDU-KATA, 2019)
The research aimed to (1) describe the process of developing the Indonesian Student Workheet using Problem Based Learning Model, (2) show the quality of the Indonesian Student Work Sheet using Problem Based Learning Model, including: (a) the product quality of the Student Worksheet and (b) the using quality of the Student Worksheet. The type of the research was research and development using 4-D model, those are definition, design, development, and dissemination. The data collection used instrument of validation sheet from the expert, questionnaire sheet, observation sheet. The technique of data analysis divided into three, the technique of data analysis of student worksheet quality and the implementation of student work sheet using Problem Based Learning. The results showed that the development process consisted of two stages: (1) the analysis phase of the writer’s understanding about the Student Worksheet and it’s need, and (2) the design phase which produced the summaries of the materials in each basic competences. The product quality based on the expert gained the score in average of 72.48%, good, the using quality based on the questionnaires to the teacher and observation to the students gained the score in average of 75, 65, good.